Measurement of angular and linear segmental lumbar spine flexion-extension motion by means of image registration - Penning, L. (Springer-Verlag, 2004)
BACKGROUND: The presently available method of measuring segmental lumbar spine mobility by means of superimposition of lumbar spine radiographs in flexion and extension lacks precision due to differences in the cortical outline of the vertebral bodies in flexed and extended position. The introduction of digital image processing has opened the possibility of computerised superimposition (‘matching’) of digital vertebral body images by means of image registration. Theoretically this technique allows more accurate image matching and, consequently, greater precision of measurement because the whole vertebral body image (not only its cortical outline) can be chosen as region of interest, with registration of all available digital information within this region. METHODS: To check accuracy and convenience of the new method, two computer program experts performed five image registration measurements of the five lumbar motion segments in five consecutive flexion-extension studies of old lumbar fracture, spondylolytic spondylolisthesis and degenerative anterolisthesis. For comparison an experienced radiologist performed the same repeated measurements with the manual superimposition method. RESULTS: Measurement error of the image registration method proved to be significantly smaller than that of the manual superimposition method. There was no overlap between the 95% confidence intervals of the mean standard deviations of experts A and B using the image registration method and the 95% confidence interval of the mean standard deviations of the experienced radiologist using the manual superimposition method. Besides, the image registration method proved to be more convenient because the whole procedure from import of the image data to display of the measurement outcomes lasted 2–3 min compared to 3–6 min for the superimposition method.